Potential Drug-Drug and Drug-Disease interactions of selected experimental therapies used in treating COVID-19 patients - Al-Zidan, Radhwan Nidal (Journal of Drug Delivery and Therapeutics, 2020)
At the end of 2019, the whole world was witnessing the birth of a new member of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) family in Wuhan city, China. Since then, the 2019 novel coronavirus (COVID-19) has rapidly invaded every corner of the world. Before the end of September 2020, nearly 32 million cases worldwide were recorded, with a death toll of approximately 1 million cases. As COVID-19 has spread across the world, certain groups of people prove more susceptible than others. Elderly patients and people with chronic medical conditions such as heart disease or diabetes are more likely to experience or even suffer from serious diseases. As a population, senior citizens take more medicines than young people. Similarly, people with chronic illnesses who are several taking drugs to control their illness. All this poses a significant query in managing COVID-19 cases: can a standard drug regimen be paired with one or more experimental drugs? For example, some of the most widely prescribed medicines—including antibacterial drugs, antifungals, heart-related medications, neuroleptics, contraceptives, and sedatives —can have extensive and often even severe interactions with some of the experimental COVID-19 therapy. Therefore, to reduce the morbidity and mortality rate associated with COVID-19, this issue needs to be answered in detail. This review addressed the key points related to the drug-drug and drug-disease interaction in patients with COVID-19. To help health care providers locate the answers they need in the shortest possible time, the information contained in this review has been included in easy-to-read tables. Keywords: Drug interactions; DDIs; Polypharmacy; SARS-CoV-2; COVID-19.